Transcutaneous electrical acupoint stimulation induced sedative effects in healthy volunteers: A resting-state fMRI study - Lu, Zhihong; Huo, Tingting; Deng, Jiao; Guo, Fan; Liu, Kang; Liu, Peng; Wang, Qiang; Xiong, Lize (Frontiers in Human Neuroscience, 2023)
Background: Previous studies indicated sedative effect of acupoint stimulation. However, its mechanism remains unclear. The aim of this study was to investigate the sedative effect of transcutaneous electrical acupoint stimulation (TEAS), and to explore the brain regions involved in this effect in healthy volunteers using functional magnetic resonance imaging (fMRI) techniques. Methods: In this randomized trial, 26 healthy volunteers were randomly assigned to TEAS (receiving 30 min of acupoint stimulation at HT7/PC4) and Control group. fMRI was conducted before and after intervention. Primary outcome was BIS value during intervention. Secondary outcomes included amplitude of low-frequency fluctuation (ALFF) and region of interest (ROI)-based functional connectivity (FC) showed by fMRI. Results: In healthy volunteers, compared with Control group, ALFF values of patients in the TEAS-treated volunteers decreased in the left thalamus, right putamen and midbrain, while increased in the left orbitofrontal cortex. More FC existed between the thalamus and the insula, middle cingulate cortex, somatosensory cortex, amygdala and putamen in subjects after TEAS treatment as compared to subjects that received non-stimulation. In addition, ALFF values of the thalamus positively correlated with BIS in both groups. Conclusion: TEAS could induce sedative effect in healthy volunteers, and inhibition of the thalamus was among its possible mechanisms. Clinical Trial registration: ClinicalTrials.gov (NCT01896063, registered July 2013)